2022
DOI: 10.1159/000524398
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Predictors of Success of EUS-B-FNA in the Diagnosis of Pulmonary Malignant Lesions: A Prospective Multicenter Italian Study

Abstract: <b><i>Background:</i></b> The role of endoscopic ultrasound with bronchoscope fine-needle aspiration (EUS-B-FNA) in the diagnosis of suspected malignant pulmonary lesions adjacent to the esophagus has been poorly investigated. The aim of the present study was to assess the accuracy of EUS-B-FNA for the diagnosis and molecular profiling of paraesophageal pulmonary lesions, as well as its predictors of success. <b><i>Materials and Methods:</i></b> Patients who unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Among the included studies, 17 were full-text articles [ 10 - 17 , 20 - 28 ], while 2 were conference abstracts [ 18 , 19 ]. Based on the study design, 6 studies were prospective [ 11 , 13 , 18 , 24 , 26 , 27 ], and the remaining 13 were retrospective [ 10 , 12 , 14 - 17 , 19 - 23 , 25 , 28 ]. The diagnostic test was EUS-FNA/FNB in 15 studies [ 10 - 21 , 24 , 25 , 28 ] and EUS-B-FNA [ 22 , 23 , 26 , 27 ] in 4 studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the included studies, 17 were full-text articles [ 10 - 17 , 20 - 28 ], while 2 were conference abstracts [ 18 , 19 ]. Based on the study design, 6 studies were prospective [ 11 , 13 , 18 , 24 , 26 , 27 ], and the remaining 13 were retrospective [ 10 , 12 , 14 - 17 , 19 - 23 , 25 , 28 ]. The diagnostic test was EUS-FNA/FNB in 15 studies [ 10 - 21 , 24 , 25 , 28 ] and EUS-B-FNA [ 22 , 23 , 26 , 27 ] in 4 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the study design, 6 studies were prospective [ 11 , 13 , 18 , 24 , 26 , 27 ], and the remaining 13 were retrospective [ 10 , 12 , 14 - 17 , 19 - 23 , 25 , 28 ]. The diagnostic test was EUS-FNA/FNB in 15 studies [ 10 - 21 , 24 , 25 , 28 ] and EUS-B-FNA [ 22 , 23 , 26 , 27 ] in 4 studies. Ten studies used only a 22-G needle [ 10 - 12 , 14 , 16 , 21 , 22 , 24 - 26 ], 7 studies used a variety of needle sizes ranging from 19-25-G [ 15 , 17 , 18 , 20 , 23 , 27 , 28 ], and 2 studies did not report the type of needle used [ 13 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent multicentric study from Italy reported the efficacy and safety of EUS-guided tissue sampling as a minimally invasive procedure for the diagnosis and staging of peri-oesophageal parenchymal lung lesions. [ 2 ] However, transoesophageal FNA from lung mass may be rarely associated with pneumothorax[ 3 ] and haemoptysis. [ 4 ] Hence, a check X-ray should be done to rule out pneumothorax before discharging the patient.…”
mentioning
confidence: 99%